ANXIETY LEVELS AND PERCUTANEOUS CARDIAC INTERVENTION (PCI) IN STEMI AND NSTEMI PATIENTS AT BANGIL HOSPITAL - MERBAWANI, RARAS (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
According to the World Health Organization, coronary heart disease, including STEMI and NSTEMI, is the leading cause of noncommunicable disease-related mortality worldwide. First treatment for STEMI-NSTEMI patients was reperfusion with Percutaneous Coronary Intervention (PCI). Anxiety increases the difficulty of controlling cardiac disease in patients with a diagnosis of STEMI and NSTEMI who will undergo PCI surgery. This study employs a cross-sectional correlation analysis methodology. Patients with coronary heart disease diagnosed with STEMI and NSTEMI who are receiving treatment at Bangil Hospital constituted the population. Forty respondents were selected using a technique called purposive sampling. Percutaneous Coronary Intervention (PCI) is the independent variable. While apprehension levels are the dependent variable. At a Sig (2-tailed) value of 0.05, Ho was rejected and H1 was accepted, indicating that there was a correlation between preparation for surgery (Giving Informed Consent) Percutaneous Coronary Intervention and anxiety levels in STEMI - NSTEMI patients at Bangil Hospital. Consent was obtained prior to the decision to perform PCI. If the patient agrees to informed consent, the procedure will continue; if the patient refuses, the procedure will not be performed. The conclusion of this study is that Percutaneous Coronary Intervention (PCI) procedures are associated with a lower level of anxiety the better the preparation for surgery (providing informed consent) is.